Chlorite-white Mica Pairs' composition as a micro-chemical guide to fingerprint massive sulfide deposits of the Bathurst Mining Camp, Canada - Mc Clenaghan, Sean; Dehnavi, Azam Soltani; McFarlane, Christopher R.M.; Lentz, David R.; Walker, James A. (My University, 2019)
The compositions of phyllosilicates, with a focus on fluid-mobile elements, were evaluated as a means to fingerprint the Middle Ordovician metamorphosed (greenschist facies) volcanogenic massive sulfide deposits of the Bathurst Mining Camp (BMC), Canada. Ninety-five drill-core samples from six of the major deposits of the Bathurst Mining Camp (Brunswick No. 12, Heath Steele B zone, Halfmile Lake Deep zone, Key Anacon East zone, Louvicourt, and Restigouche) were analyzed using electron microprobe and laser ablation inductively coupled plasma-mass spectrometry. Typically, phyllosilicates (chlorite, white mica, and to a lesser extent biotite) are ubiquitous phases in the host rocks of the massive sulfide deposits of the BMC. Electron microprobe analysis results show a wide compositional variation in chlorite and white mica. Laser ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS) analysis was performed to measure fluid-mobile elements, showing that Tl is distinctly enriched in all white mica (up to 719 ppm) relative to chlorite (up to 50.1 ppm). Chlorite hosts Sn (up to 4600 ppm), Hg (up to 7.3 ppm), Sb (up to 35.4 ppm), As (up to 1320 ppm), In (up to 307 ppm), Cd (up to 83.2 ppm), and Se (up to 606 ppm). White mica hosts Sn (up to 1316 ppm), Hg (up to 93 ppm), Sb (up to 1630 ppm), As (up to 14,800 ppm), In (up to 1186 ppm), Cd (up to 98 ppm), and Se (up to 38.8 ppm). Limited LA-ICP-MS analysis on biotite indicates a higher overall concentration of Tl (mean = 14.6 ppm) relative to co-existing white mica (mean = 2.18 ppm). On average, biotite is also more enriched in Hg, Sn, and Ba relative to chlorite and white mica. Laser Ablation ICP-MS profiles of chlorite, white mica, and biotite demonstrate smooth time-dependent variations diagnostic of structural substitution of these elements. Compositional variation of chlorite-white mica pairs presented in the current study shows systematic variations as a function of distance from the mineralized horizons. This highlights the potential to use trace-element signatures in these phyllosilicate pairs to identify proximal (chlorite) and distal (white mica) footprints for volcanogenic massive sulfides exploration.
PUBLISHED
Keywords: Bathurst Mining Camp (BMC); Biotite; Chlorite; Fingerprint; Fluid-mobile elements; LA-ICP-MS; Massive sulfide deposit (VMS); Phyllosilicate; Vectoring tool; White mica